Determinant Profitability and Liquidity Analysis of Expressions Islamic Social Reporting in Sharia Commercial Banks - Izzun Khoirun Nissa; M.Yunan Hidayat; Chusnul Intan; Jessica; Rosida Dwi Ayuningtyas (El-Qish: Journal of Islamic Economics, 2023)
This study aims to explain the variables of profitability and liquidity on the expression of Islamic social reporting at Islamic commercial banks in Indonesia for the period 2018 to 2021. The population in this study is Islamic banking in Indonesia registered with the Financial Services Authority (OJK) for the period 2018 – 2021. The data used in this study is panel data from 9 selected Islamic banks, with a total sample of 36. Profitability has a negative and significant effect on ISR expression. This means that the greater the profitability in Islamic banks, the narrower the ISR disclosure will be made. Meanwhile, liquidity hurts ISR expression.  which means that when liquidity is high, it will also be narrower in the ISR disclosures made. So, it can be concluded that Islamic banking in Indonesia needs to pay attention to ISR expressions that are carried out to also trust the community.